The Current State of Education in Madagascar: Challenges and Solutions - Razanamiariso, Rakotomalala Nivomboahangy; Baholy, Robijaona Rahelivololoniaina (BIRCU, 2023)
The first Missionary Station in Isoavina was established in the early years, with the initial school providing basic education and extracurricular activities, such as crafting, woodwork, and iron modeling, during the years 1870-1877. The school was known as the